2015
DOI: 10.1080/15384101.2015.1120916
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 is required for Aurora B activation in cell mitosis and spindle checkpoint

Abstract: y These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Recent studies reported that overexpressed Skp2 was found in paclitaxel-resistant prostate cancer cells ( Yang et al, 2016 ; Byun et al, 2018 ; Gong et al, 2018 ), and knockdown of Skp2 restored the sensitivity of paclitaxel in prostate cancer cells ( Byun et al, 2018 ). Skp2 also plays a pivotal role in mitosis and spindle checkpoint by triggering ubiquitination and activation of Aurora-B ( Nakayama et al, 2004 ; Sugihara et al, 2006 ; Hu and Aplin, 2008 ; Wu et al, 2015 ). Skp2 depletion in melanoma cells resulted in a G2-M phase arrest ( Hu and Aplin 2008 ), and suppression of both BRAF (V600E) and Skp2 inhibited cell growth and invasion in melanoma cell lines( Sumimoto et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that overexpressed Skp2 was found in paclitaxel-resistant prostate cancer cells ( Yang et al, 2016 ; Byun et al, 2018 ; Gong et al, 2018 ), and knockdown of Skp2 restored the sensitivity of paclitaxel in prostate cancer cells ( Byun et al, 2018 ). Skp2 also plays a pivotal role in mitosis and spindle checkpoint by triggering ubiquitination and activation of Aurora-B ( Nakayama et al, 2004 ; Sugihara et al, 2006 ; Hu and Aplin, 2008 ; Wu et al, 2015 ). Skp2 depletion in melanoma cells resulted in a G2-M phase arrest ( Hu and Aplin 2008 ), and suppression of both BRAF (V600E) and Skp2 inhibited cell growth and invasion in melanoma cell lines( Sumimoto et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo ubiquitination assay was performed as described elsewhere 51. In brief, 293T cells were transiently transfected with indicated plasmids for 36 h. Transfected cells were harvested by denatured buffer (6 M guanidine-HCl, 0.1 M Na 2 HPO 4 /NaH 2 PO 4 , 10 mM imidazole).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the proteolytic function of SKP2, recent studies have revealed that SKP2 exerts its oncogenic activity by mediating the conjugation of lysine-63 (K63)-linked polyubiquitin chains to target proteins such as protein kinase B (PKB; also known as AKT) [42], Yes-associated protein (YAP) [43], Twist transcriptional factor [44], Nijmegen breakage syndrome 1 (NBS1) [45], Ras related GTP binding A (RAG-A) [46], Breakpoint cluster region-Abelson (BCR-ABL) [47], human MutT homolog 1 (MTH1) [48], and Aurora-B [49], which results in the stabilization or alters the localization of these proteins or promotes the recruitment of interactors. The K63-linked ubiquitylation of the protein kinase AKT by SCF SKP2 is stimulated by growth factors and cytokines, and it facilitates the recruitment of AKT to the plasma membrane, with its resulting hyperactivation leading to up-regulation of glycolysis and promotion of tumorigenesis [42,50].…”
Section: Fbxl1 (Skp2)mentioning
confidence: 99%